2016
DOI: 10.2105/ajph.2016.303155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Affordable Care Act on Racial and Ethnic Disparities in Health Insurance Coverage

Abstract: The ACA has reduced racial/ethnic disparities in coverage, although substantial disparities remain. Further increases in coverage will require Medicaid expansion by more states and improved program take-up in states that have already done so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
235
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(243 citation statements)
references
References 22 publications
7
235
1
Order By: Relevance
“…Our findings suggest that larger gains in insurance coverage for some minority groups observed among the overall adult population were not driven by differential take-up of Medicaid among newly eligible adults. Estimates from the American Community Survey reported in a recent study that simultaneously stratifies on race, income, and state expansion status also suggest that differences in Medicaid take-up across racial and ethnic groups did not closely resemble changes in the uninsurance rate for individuals of all income levels in all states (Buchmueller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that larger gains in insurance coverage for some minority groups observed among the overall adult population were not driven by differential take-up of Medicaid among newly eligible adults. Estimates from the American Community Survey reported in a recent study that simultaneously stratifies on race, income, and state expansion status also suggest that differences in Medicaid take-up across racial and ethnic groups did not closely resemble changes in the uninsurance rate for individuals of all income levels in all states (Buchmueller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Across all states and income groups, young adults experienced larger reductions in uninsurance between 2013 and 2014 than did older adults, and larger gains in insurance coverage have also been documented for Black and Hispanic adults relative to white adults (Buchmueller et al, 2016;Courtemanche, Marton, and Yelowitz, 2016;McMorrow et al, 2015a;McMorrow et al, 2015b).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined the effects of the ACA expansions on the general population, finding gains similar to those of our noncancer history subgroup. 15,18,20 One previous study by Parsons et al 27 focused on the coverage effects of the 2010 expansions that allowed young adults up to age 26 to be covered on a parent’s family policy. That study found higher coverage rates among young adults newly diagnosed with cancer compared with a slightly older group who could not be covered under a parent policy.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The decrease was evident in all states and sociodemographic groups though more pronounced for adults in states that expanded Medicaid, 16,17 in persons with low socioeconomic status, and in racial and ethnic minorities. 18,19 The decline in uninsured rates nationally comes from a 5.5 percentage point increase in private coverage, and a 2.2 percentage point increase in public (Medicaid) enrollment. 20 …”
mentioning
confidence: 99%